Fracture resistance of weakened bovine teeth after long-term use of calcium hydroxide - Valera, Marcia Carneiro [UNESP]; Albuquerque, Maria Tereza Pedrosa [UNESP]; Yamasaki, Mayra Cristina; Vassallo, Flávia Nicolle Stefani [UNESP]; Silva, Denise Almeida e Silva Alves da [UNESP]; Nagata, Juliana Yuri (Wiley-Blackwell, 2015)
In some parts of the world, revascularization may not be the most feasible treatment option for necrotic immature teeth. Therefore, apexification remains the most widely utilized treatment option for these cases. This study aimed to evaluate the fracture resistance of weakened bovine tooth roots treated with various irrigant solutions as well as long-term application of calcium hydroxide intracanal medication (ICM). One hundred seventy bovine teeth were randomly divided into three experimental groups (n = 50) and two control groups (n = 10). Group SS was irrigated with physiologic solution; group CHX was treated with 2% chlorhexidine gel and group NaOCl was irrigated with 1% sodium hypochlorite. After instrumentation, root canals were dressed with calcium hydroxide and evaluated at different periods (15, 60, 90, 180, and 360 days). The specimens were loaded at a 45° angle to measure fracture resistance through the use of an EMIC test machine. A decrease in fracture resistance was observed during the time of ICM dressing. The highest values of fracture resistance were observed in group SS with 15 days of ICM, not differing from the control group. Irrigation with NaOCl associated with ICM for 15 days presented the lowest fracture resistance; however, a statistically significant difference was not observed when compared with SS and CHX in the same time period. In longer periods of exposure to ICM (180 and 360 days), root canals irrigated with NaOCl and CHX showed significantly lower fracture resistance than SS (P < 0.05). Apexification with periodic changes of calcium hydroxide medicament leads to weakness of the teeth independent of the irrigation solution used.
Keywords: Calcium hydroxide; Fracture resistance; Irrigant solution; Permanent tooth; Prognosis; Root fracture